Aspect Physiology Plant of Cauliflower (Brassica oleracea var botrytis L.) in the Interval of Nitrogen Fertilization, Dose and Type of Organic Fertilizer in Coastal Sandy Land - Supriyanto, Supriyanto; Saparso, Saparso; Rif'an, Muhammad (PLANTA TROPIKA: Jurnal Agrosains (Journal of Agro Science), 2020)
Cauliflower is one of the vegetables that have the ability to adapt to coastal sandy land. Cauliflower production can be increased by extensification efforts using coastal sandy land. The research aimed to determine the type of liquid organic fertilizer, the fertilization interval of liquid organic fertilizer, and the appropriate dose of nitrogen fertilizer for the growth and productivity of cauliflower plant on coastal sandy land. The research was conducted in Jetis sandy beach, Banjarsari Village, Nusawungu Sub-district, Cilacap Regency. The study was conducted from August 2017 to November 2017. The experiment was arranged in a Factorial Randomized Complete Block Design (RCBD). Data were analyzed by F test followed by DMRT 5%. The results showed that (1) type of artificial liquid organic fertilizer gave best result on the dry root weight and chlorophyll b. (2) The 9-day-interval of liquid organic fertilizer application interval gave the best result on the fresh root weight and fresh plant weight, while the 4-day-interval of liquid organic fertilizer application gave the best result on dry flower weight. (3) The doses of N fertilizer significantly affected leaf area, root volume, fresh root weight, fresh leaf weight, dry leaf weight, fresh plant weight, dry plant weight, fresh stem weight, dry stick weight, fresh flower weight, flower weight dry, and flower diameter.